(untitled) (Journal of Economic Research & Business Administration, 2016)
The article deals with the enterprise risk-management problems. The authors analyze development of assessment methodology and management of risks of innovative projects and the basic levels of risk management; they give the matrix of key components of the enterprise risk management process. This concept allows to deal successfully with incipient problems and use the opportunities increasing the enterprise potential.